2021
DOI: 10.3390/jcdd9010003
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Cardiovascular Risk Factors and Hypogonadism on Cardiac Outcomes in an Aging Population of Beta-Thalassemia Patients

Abstract: Beta-thalassemia major (β-TM) is a hereditary genetic disease worsened by many comorbidities due to transfusion-related iron despite chelation therapy. Since there has recently been an increase in life expectancy of patients to up to 50 years old, which influences the prevalence of these diseases and the time span for traditional cardiovascular risk factors to play their role, this study aims to evaluate their distribution and prevalence in a population of thalassemia major patients and their relationship with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Adequate awareness of cardiovascular disease is a prerequisite for the adoption of preventive actions and healthy behaviors, and it is particularly important for TM patients due to the heavy burden of CVD, which is associated with multiple causes (myocardial iron overload, traditional cardiovascular risk factors, cardiovascular inflammation, and fibrosis) [10][11][12][13][14]. This is the first study evaluating gender differences in knowledge and awareness of CVDs, knowledge of CVRFs and preventive measures, and perception of health status among Italian patients with TM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate awareness of cardiovascular disease is a prerequisite for the adoption of preventive actions and healthy behaviors, and it is particularly important for TM patients due to the heavy burden of CVD, which is associated with multiple causes (myocardial iron overload, traditional cardiovascular risk factors, cardiovascular inflammation, and fibrosis) [10][11][12][13][14]. This is the first study evaluating gender differences in knowledge and awareness of CVDs, knowledge of CVRFs and preventive measures, and perception of health status among Italian patients with TM.…”
Section: Discussionmentioning
confidence: 99%
“…Besides MIO, in TM, heart disease can also result from other causes such as chronic anemia, endocrine abnormalities [10,11], nutritional deficiencies, and genetic factors [12,13]. It has been shown that in TM diabetes mellitus significantly increases the risk for heart failure (HF), hyperkinetic arrhythmias, and myocardial fibrosis, independently from MIO [11].…”
Section: Introductionmentioning
confidence: 99%
“…Its prevalence varies among studies, related especially to whether or not the pubertal status is taken into consideration. Long-term hypogonadism induces a high cardiovascular risk in addition to toxic effects of cardiac IO [ 53 ]. According to one study, the prevalence is 23.6% among patients at puberty age, and ferritin negatively correlates with pituitary volume [ 27 ].…”
Section: Thalassemic Endocrine Diseasementioning
confidence: 99%
“…It presents with hemolytic anemia caused by abnormalities in the synthesis of beta chains of hemoglobin [ 98 ]. Despite the presence of anemia, which is caused by ineffective erythropoiesis, elevated iron and ferritin levels are observed [ 99 ]. Such disruptions of iron metabolism are caused by the necessity of life-long blood transfusions in the patient [ 99 ].…”
Section: Iron Metabolism Disorders As the Trigger Of Oxidative Stressmentioning
confidence: 99%
“…Despite the presence of anemia, which is caused by ineffective erythropoiesis, elevated iron and ferritin levels are observed [ 99 ]. Such disruptions of iron metabolism are caused by the necessity of life-long blood transfusions in the patient [ 99 ]. Kukongviriyapan et al, while conducting a study among 22 patients suffering from beta thalassemia, proposed that the auto-oxidation of excess beta globin chains and iron accumulation leads to oxidative stress and subsequent tissue and organ damage [ 100 ].…”
Section: Iron Metabolism Disorders As the Trigger Of Oxidative Stressmentioning
confidence: 99%